NARASI KONTRA TERORISME PADA LITERATUR INDONESIA DAN ANIMASI FIKSI POPULER - Adania, Luthfina; Zuhdi, Muhammad Luthfi (Academic Journal of Islamic Principles and Philosophy, 2023)
The author explores the potential of fictional media in counter-terrorism efforts, especially as an antidote to the spread of pro-terrorism narratives. Fiction media has the potential to bridge differences by spreading universal values that can transcend language, geography, and cultural boundaries. Multicultural culture helps teach tolerance and respect for one another. The method used is a literature study of previous research results. The selected studies used fiction and memoirs from Indonesia, as well as popular fiction from abroad, namely Avatar: The Legend of Aang and Fullmetal Alchemist. The conclusion of this research is that providing a sense of group or brotherhood arising from the similarity of favorite fictional media can transfer values that counteract the spread of terrorism. Lastly, there are suggestions for parents, teachers, and other stakeholders on how to select entertainment media that has counter-terrorism values to become learning media for children and adolescents based on the interests of the target audience, reviews from other adults, and ratings determined by government regulations.